The use of five-finger relaxation techniques for reducing stress and sleep quality in hypertension patients - Dewi, Rosliana; Budhiana, Johan; Arsyi, Dilla Nurul; Yulianti, Maria; Fatmala, Syiva Dwi (JHeS (Journal of Health Studies), 2023)
One of the efforts to overcome hypertension experienced by its sufferers is to reduce stress and improve their sleep quality. Patients will usually overcome hypertension by taking drugs (which are chemical). Some use alternative methods. However, not many studies have been conducted to reveal efforts to reduce stress and improve sleep quality in hypertensive patients through this alternative method. It is the main reason research is carried out on non-pharmacological efforts to overcome stress and improve sleep quality that is effective, easy, and can be done alone by patients. This study aimed to determine the effect of five-finger relaxation techniques on stress and sleep quality in hypertensive patients in the working area of the Sukabumi Health Center. This study was a quasi-experiment with two groups of pre-tests and post-tests. The population and sample were hypertensive patients in the working area of the Sukabumi Health Center, with as many as 70 respondents divided into control and intervention groups of 35 respondents, each using purposive sampling techniques. The DASS-42 standard questionnaire was used for stress variables, while the PSQI standard questionnaire was used for sleep quality variables.Â Data analysis using a paired sample t-test showed differences in the pre-test and post-test stress scores in the control and intervention groups and in the control and intervention groups' sleep quality scores in the pre-test and post-test. The five-finger relaxation technique can lower hypertensive patients' stress and sleep quality scores. This technique is also an easy, inexpensive technique that is very likely to be done by hypertensive patients to maintain stable blood pressure and is an alternative non-pharmacological therapy for overcoming stress problems and sleep quality in hypertensive patients.